A hybrid lightweight security approach in internet of things for healthcare application - Ameer Saad Kadhim; Ali Haider Alazam; Noor Fahem Sahib (Institute of Advanced Engineering and Science, 2022)
The internet of things (IoT) is a rapidly developing area that consists of a globally linked network architecture based on the Internet. The internet of healthcare things (IoHT) is a subset of IoT that comprises of smart healthcare devices that are critical in monitoring, processing, storing, and transferring sensitive data. It is confronted with new issues in terms of data privacy protection. To safeguard healthcare information, this work proposes hybrid lightweight ciphers (PRESENT and TEA) that leverage elliptic curve cryptography (ECC) in the key generation phase. The proposed system evaluated using the main network evaluation parameters as throughput in Kbps, delay in ms, packet loss rate (%). The proposed approach provides secure data transmission of IoT devices based on the used lightweight security algorithms, in addition it provides conserving network performance, improving channel resource usage, network latency is increased due to the security level added by PRESENT and TEA with ECC, and decrease number of loss packets compared without security case study.